Transferência do conhecimento do mestrado profissional em administração ao setor produtivo: considerações a partir das capacidades absortivas potenciais presentes nos trabalhos finais - Sadocco , Rafael Rodolfo Sartorelli (2025)
This thesis investigates the feasibility of knowledge transfer from the professional master's degree in Administration to the productive sector, through the theoretical lens of Potential Absorptive Capacities, by seeking to understand whether the professional master's format allows this to be achieved. In parallel, it aims to propose elements that can enhance this postgraduate modality, aspiring to contribute to methodology, theory, and companies.To this end, a qualitative, applied research was conducted, with exploratory and descriptive objectives. The research was methodologically guided by Grounded Theory, supported by thematic analysis as the structuring technique for the coding and analytical process. Regarding technical procedures, document analysis was employed, through the reading of all professional master's dissertations in Administration and Business Administration from programs evaluated by Capes with scores 4 and 5, and which were publicly available online during the research period, as well as other public data sources that allowed for assessing their applicability, such as authors’ résumés, news articles, and published works. Thus, 172 dissertations from 12 different programs were reviewed.The following categories were built, divided into three aspects: (i) those that precede the research, such as self-financing of the professional master's research and the involvement of co-supervisors (market representatives); (ii) aspects that involve the investigation, writing, and defense process of the dissertation, referring to the theoretical and methodological aspects of the investigation; the apologetic stance toward the studied company, and the writing of the final work (b) – dissertation versus essay; and (iii) aspects related to the dissertation defense and the transfer of results, which discuss university-company knowledge transfer, from the perspective of Potential Absorptive Capacities.The research concluded that knowledge transfer is limited by the lack of institutional entwinement among the various agents and by the lack of proper training of the master's students, who are unable to meet the high expectations set by the legislation regulating this modality.